2010
DOI: 10.1785/0120090320
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Bayesian Regression Analysis Applied to Ground-Motion Prediction Equations, Part 2: Numerical Example with Actual Data

Abstract: An application of a linear multivariate Bayesian regression model, described in a companion article, to obtain a ground-motion prediction equation (GMPE) using a set of actual ground-motion records and a realistic functional form is presented. Based on seismological grounds and on an adopted functional form, we include a sound discussion about how the prior information required for the model can be defined. For the regression analyses we use two subsets of ground-motion records from the Next Generation of Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Although the current practice estimates the GMM for each IM individually and then assess the cross‐IM correlation coefficients/models separately, several studies have shown that it is possible but challenging to incorporate the spatial cross‐IM (ie, considering both spatial correlation and cross‐IM correlation at the same time) in the GMM estimation process, requiring often stricter assumptions. The developed one‐stage estimation approach can also account for the cross‐IM correlation, and this feature is currently under investigation by the authors, especially in terms of implications on the GMM estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Although the current practice estimates the GMM for each IM individually and then assess the cross‐IM correlation coefficients/models separately, several studies have shown that it is possible but challenging to incorporate the spatial cross‐IM (ie, considering both spatial correlation and cross‐IM correlation at the same time) in the GMM estimation process, requiring often stricter assumptions. The developed one‐stage estimation approach can also account for the cross‐IM correlation, and this feature is currently under investigation by the authors, especially in terms of implications on the GMM estimates.…”
Section: Methodsmentioning
confidence: 99%
“…We have not included a sound discussion because a synthetic example is presented. In a companion article (Arroyo and Ordaz, 2010) we use a set of actual ground-motion records and we present a complete discussion on how the prior information can be defined.…”
Section: Prior Information For the Bayesian Methodsmentioning
confidence: 99%
“…Earthquakes from this catalog were selected from January 1 st , 1976 to December 31, 2014, within the geographic coordinates 15ºN ≥ latitude ≤ 24ºN latitudes and 106ºW ≤ longitude ≥ 92º W. All the events have magnitudes Mw ≥ 4.7 and focal depths of less than 40 km. In this case, the GMPE's estimated by Arroyo and Ordaz, (2010). for subduction zone earthquakes were utilized.…”
Section: Attenuation Modelsmentioning
confidence: 99%